2007
DOI: 10.1159/000111998
|View full text |Cite
|
Sign up to set email alerts
|

The Cortical Involvement of Territorial Infarcts as a Risk Factor for Stroke-Related Seizures

Abstract: Background: The cortical involvement of territorial infarcts is considered to be a significant risk factor for the development of early- as well as late-onset seizures. However, it is not known which cortical regions are more susceptible to the development of stroke-related seizures. Patients and Methods: In this retrospective study of 687 patients with territorial infarcts, 184 with stroke-related seizures were compared to 503 without seizures. The extent and the location of the infarcts were determined by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 57 publications
(36 reference statements)
1
12
0
Order By: Relevance
“…After ischemic stroke, NCSE was more frequently observed in the anterior versus the posterior circulation infarct [14]. Although some reports have demonstrated a correlation between SE and lobar [6] or posterior temporal [22] lesions, other studies have reported finding no relationship between localization and the occurrence of SE [2,3,13]. Outcomes at discharge and the mortality rates were not significantly different between the CSE and NCSE groups.…”
Section: Discussionmentioning
confidence: 72%
“…After ischemic stroke, NCSE was more frequently observed in the anterior versus the posterior circulation infarct [14]. Although some reports have demonstrated a correlation between SE and lobar [6] or posterior temporal [22] lesions, other studies have reported finding no relationship between localization and the occurrence of SE [2,3,13]. Outcomes at discharge and the mortality rates were not significantly different between the CSE and NCSE groups.…”
Section: Discussionmentioning
confidence: 72%
“…Early-onset stroke is more common in infarctions due to occlusion of anterior circulation than those originating from the posterior system [12]. The mechanism underlying seizure in patients with posterior system infarctions is unclear.…”
Section: Case Reportmentioning
confidence: 99%
“…26 Repeated seizures or epilepsy, following any kind of ischaemic stroke, leads to a significantly lower mean MMSE score. 27 also in patients with late-onset cryptogenic seizures positron emission tomography (PET) examination suggests that they could represent the premonitory signs of a progressive encephalopathy leading to cognitive impairment.…”
Section: Vascular Cognitive Impairment and Seizuresmentioning
confidence: 99%